Annotated Statutes of the Indian Territory: Embracing All Laws of a General and Permanent Character in Force at the Close of the Second Session of the Fifty-fifth Congress, at 228, § 1149 (1899) - (:unkn) unknown (General Publisher, 1868)
Every person who shall draw a pistol, gun or any other deadly weapon upon any other person, for the purpose of frightening or intimidating him from doing or attempting to do any lawful act, when such person drawing said pistol, gun or other deadly weapon is not justified in self-defense for so doing, shall be deemed guilty of a misdemeanor, and, upon conviction, shall be fined in a sum not less than five hundred dollars nor more than one thousand dollars and be imprisoned in the county jail for twelve months.
--
Keywords: BRANDISHING